2008
DOI: 10.1002/hyp.7012
|View full text |Cite
|
Sign up to set email alerts
|

Predicting longitudinal dispersion coefficient in natural streams by artificial intelligence methods

Abstract: Abstract:In this study, three artificial neural network methods, i.e. feed forward back propagation, the radial basis function neural network, and the generalized regression neural network are employed to compute the longitudinal dispersion coefficient in order to evaluate its behaviour in predicting dispersion characteristics in natural streams. These methods, which use hydraulic and geometrical data to predict dispersion coefficients, can easily be applied to natural streams and are proven to be superior in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 80 publications
1
49
1
Order By: Relevance
“…Artificial neural networks constitute a useful tool to predict and forecast various hydrological variables and are used extensively in water resources research (Tayfur, 2002;Cigizoglu, 2003aCigizoglu, ,b, 2004Sudheer, 2005;Cigizoglu & Kisi, 2006;Toprak & Cigizoglu, 2008). The ANN models are frequently employed for rainfall forecasting (Hsu et al, 1997;Kulligowski & Barros., 1998;Hall, 1999;Silverman & Dracup, 2000;Applequist et al, 2002;Ramirez et al, 2005;Freiwan & Cigizoglu, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks constitute a useful tool to predict and forecast various hydrological variables and are used extensively in water resources research (Tayfur, 2002;Cigizoglu, 2003aCigizoglu, ,b, 2004Sudheer, 2005;Cigizoglu & Kisi, 2006;Toprak & Cigizoglu, 2008). The ANN models are frequently employed for rainfall forecasting (Hsu et al, 1997;Kulligowski & Barros., 1998;Hall, 1999;Silverman & Dracup, 2000;Applequist et al, 2002;Ramirez et al, 2005;Freiwan & Cigizoglu, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The presented work is an extension and generalization of previous studies (Kashefipour et al, 2002;Toprak & Cigizoglu, 2008) including some works of the authors (Wallis & Manson, 2004;Rowinski et al, 2005) in which predictions of dispersion coefficients were made based on previous tracer experiments performed in similar river reaches. In Piotrowski et al (2007) neural network predictions of the whole breakthrough curves on a single river under various river conditions were studied.…”
Section: Introductionmentioning
confidence: 71%
“…Wallis & Manson, 2004), or neural network-based models (Kashefipour et al, 2002;Rowinski et al, 2005;Tayfur, 2006;Toprak & Cigizoglu, 2008) for estimating dispersion coefficients, but they all require relatively detailed knowledge about the characteristics of the considered river reaches. In this study, an attempt is made to determine the reach average longitudinal dispersion coefficient, K L , and the velocity, U, when the results of tracer tests and/or detailed hydraulic studies are not available; hence, the methods suggested in the papers cited above cannot be applied.…”
Section: Development Of Parameter Estimation Modelsmentioning
confidence: 99%
“…Other common applications of machine learning methods include: forecasting of non-stationary hydrological time series using dynamically driven recurrent neural networks, [20] prediction of longitudinal dispersion coefficients in natural streams using different types of neural networks, [21] the use of quantile regression forests to determine sediment transport, [22] downscaling of stream-flow using relevance vector machines, [23] using support vector regression to predict seasonal winter extreme precipitation, [24] and downscaling of maximum and minimum temperatures, [25] wind speeds, [26] and daily precipitation [27] using Bayesian neural networks.…”
Section: Related Workmentioning
confidence: 99%